Teaching English As A Lingua Franca: Indonesia EFL Teachers' Views - Rahayu, Gupuh (Faculty Of Education, 2023)
As the demand for English mastery grows in this globalization period, an English teacher takes the lead in students' learning progress since English as a foreign language has become the primary source of language input in many countries. Meanwhile, ELF as an English development emerging in South-East Asia may assist EFL teachers in presenting their teaching learning content in EFL classrooms. This study intends to analyze Indonesia EFL instructors' attitudes regarding teaching English as a Lingua Franca, as well as how EFL instructors' perceptions about the emerging ELF have lately changed. The researcher obtained the perspectives of EFL teachers about teaching English as a Lingua Franca through a survey study. The questionnaire, which served as the study's data source, was distributed to 15 EFL teachers in Tulungagung. The researcher also interviewed some of those teachers. The majority of EFL teachers who participated in this study had little knowledge of ELF, although more than half agreed with the statement that defined ELF. Participants regard ELF as an exciting evolution of English that will bring a new performance to their teaching and learning classrooms.